Treatment of Urethral Strictures from Irradiation and Other Nonsurgical Forms of Pelvic Cancer Treatment - Iyad Khourdaji; Jacob Parke; Avinash Chennamsetty; Frank Burks (Advances in Urology)
Radiation therapy (RT), external beam radiation therapy (EBRT), brachytherapy (BT), photon beam therapy (PBT), high intensity focused ultrasound (HIFU), and cryotherapy are noninvasive treatment options for pelvic malignancies and prostate cancer. Though effective in treating cancer, urethral stricture disease is an underrecognized and poorly reported sequela of these treatment modalities. Studies estimate the incidence of stricture from BT to be 1.8%, EBRT 1.7%, combined EBRT and BT 5.2%, and cryotherapy 2.5%. Radiation effects on the genitourinary system can manifest early or months to years after treatment with the onus being on the clinician to investigate and rule-out stricture disease as an underlying etiology for lower urinary tract symptoms. Obliterative endarteritis resulting in ischemia and fibrosis of the irradiated tissue complicates treatment strategies, which include urethral dilation, direct-vision internal urethrotomy (DVIU), urethral stents, and urethroplasty. Failure rates for dilation and DVIU are exceedingly high with several studies indicating that urethroplasty is the most definitive and durable treatment modality for patients with radiation-induced stricture disease. However, a detailed discussion should be offered regarding development or worsening of incontinence after treatment with urethroplasty. Further studies are required to assess the nature and treatment of cryotherapy and HIFU-induced strictures.